Clinical profile, treatment, and outcomes of testicular cancer in a resource-limited setting: a study from Sudan - Eltahir Ahmed Eltahir; Sami Mahjoub Taha Awad; Yassin Mohammed Osman; Mohammed El Imam Mohammed Ahmed; Moawia Mohammed Ali Elhassan (African Journal of Urology)
Abstract Background Testicular cancer is a rare malignancy, with limited data on its clinical characteristics and outcomes in Africa. This study aims to provide baseline information on the clinical presentation, treatment, and outcomes of testicular cancer in Sudan, a low-income African nation. Methods A retrospective review was conducted at two tertiary care centers in central Sudan. Data were extracted for patients > 15 years of age diagnosed with testicular cancer from 2007 to 2015, with a follow-up of up to 5 years. Patients were identified from hospital records at the National Cancer Institute and Gezira Hospital for Renal disease and Surgery. Results The study included 50 patients with a mean age of 41.9 years (SD = 18.9). Testicular swelling was the most common presenting symptom, reported in 70% of patients (n = 35). The median time from the initial complaint to diagnosis was 6 months (range: 1–36). Seminoma was the predominant histopathological subtype accounting for 68% of cases, and 64% of patients presented with advanced-stage disease (stage III). Radical orchidectomy was performed in 86% of patients. Chemotherapy was administered to 88% of patients, while 10% received radiotherapy. At the last follow-up, 44% of patients were in remission, 18% were alive with disease progression, and 36% had died. Conclusions This study highlights the high mortality rate associated with testicular cancer in this resource-limited setting, which is likely due to delayed diagnosis and the advanced stage at presentation. Enhancing health education is crucial to promote early detection and ensure timely access to care, ultimately improving patient outcomes.